Modeling ocean-induced rapid Earth rotation variations: an update - Harker, Alexander A.; Schindelegger, Michael; Ponte, Rui M.; Salstein, David A.; Institute of Geodesy and Geoinformation, University of Bonn, Bonn, Germany; Atmospheric and Environmental Research, Inc., Lexington, USA (Journal of Geodesy, 2021)
We revisit the problem of modeling the ocean’s contribution to rapid, non-tidal Earth rotation variations at periods of 2–120 days. Estimates of oceanic angular momentum (OAM, 2007–2011) are drawn from a suite of established circulation models and new numerical simulations, whose finest configuration is on a 1⁄ 6◦ grid. We show that the OAM product by the Earth System Modeling Group at GeoForschungsZentrum Potsdam has spurious short period variance in its equatorial motion terms, rendering the series a poor choice for describing oceanic signals in polar motion on time scales of less than ∼2 weeks. Accounting for OAM in rotation budgets from other models typically reduces the variance of atmosphere-corrected geodetic excitation by ∼54% for deconvolved polar motion and by ∼60% for length-of-day. Use of OAM from the 1⁄ 6◦ model does provide for an additional reduction in residual variance such that the combined oceanic–atmospheric effect explains as much as 84% of the polar motion excitation at periods < 120 days. Employing statistical analysis and bottom pressure changes from daily Gravity Recovery and Climate Experiment solutions, we highlight the tendency of ocean models run at a 1◦ grid spacing to misrepresent topographically constrained dynamics in some deep basins of the Southern Ocean, which has adverse effects on OAM estimates taken along the 90◦ meridian. Higher model resolution thus emerges as a sensible target for improving the oceanic component in broader efforts of Earth system modeling for geodetic purposes. Austrian Science Fund http://dx.doi.org/10.13039/501100002428 National Aeronautics and Space Administration http://dx.doi.org/10.13039/100000104 https://isdc.gfz-potsdam.de/ggfc-oceans/ https://doi.org/10.5281/zenodo.4707150 http://rz-vm115.gfz-potsdam.de:8080/repository/ https://ifg.tugraz.at/ITSG-Grace2018 ftp://isdcftp.gfz-potsdam.de/grace/Level-1B/GFZ/AOD/RL06/ https://ecco-group.org/products-ECCO-V4r4.htm